Aprendizados de um aluno de medicina no período de 2016 a 2023 - Barbieri, Lucas Baptistella (Universidade Federal de São Carlos, 2023)
The following work describes the trajectory of a student of Medical Course at the Federal University of São Carlos in the period from 2016 to 2023. It will be presented the experiences, growth and despairs faced in this trajectory. It aims to transmit, through a reflective analysis, the learning process, medical practice, social and professional environment, over the 7 years of the course. This narrative represents the Course Completion Work, as provided for in the Political Pedagogical Project (1), in a critical-reflexive report format, subdivided into three learning cycles and extracurricular activities; In the first cycle, reports the entry into the course, expectations, first impressions and crossed difficulties. The second cycle, reports the introduction to medical practice, patient- physician relationship. The third cycle, reports the internship routine, medical training, challenges for completing the course and how to choose a career.
Learnings of a medical student from 2016 to 2023
Keywords: Educação médica; Aprendizado baseado em problemas; Medical education; Problem based learning; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM